The Bank Lending Channel with Endogenous Money - A Simple Macro Model - Peter Spahn (Credit and Capital Markets – Kredit und Kapital, 2015)
The growth and deepening of financial markets entailed the expectation that the bank lending channel of monetary policy transmission would lose its importance. The paper explains why, on the contrary, the banking sector has become a major locus of origination and amplification of macro-financial shocks. Mutual feedback mechanisms between the financial and the real sector are analysed and simulated by using a simple standard macro model with an integrated banking system. A comparison of the efficiency of various Taylor Rule extensions explores whether monetary stabilisation can be improved by additional interest rate reactions to asset prices, bank lending, bank leverage or the spread between the loan and the policy rate. – – Der Bankkreditkanal bei endogener Geldmenge - Ein einfaches Makromodel Wachstum und Vertiefung der Finanzmärkte ließen vermuten, dass der Bank-kreditkanal der geldpolitischen Transmission an Bedeutung verlieren würde. Der Beitrag erklärt, aus welchen Gründen jedoch der Banksektor gesamtwirtschaftliche Störungen verstärkt oder sogar verursacht hat. Wechselseitige Rückwirkungseffekte zwischen dem finanziellen und dem realen Sektor der Volkswirtschaft werden anhand eines einfachen Makromodells mit integriertem Banksektor analysiert und simuliert. Vor diesem Hintergrund wird geprüft, ob die monetäre Stabilitätspolitik durch alternative Erweiterungen der Taylor-Regel verbessert werden kann: insbesondere durch zinspolitische Reaktionen auf Vermögenspreise, Volumen der Bankkredite, Bankverschuldungsgrad oder den Spread zwischen Kredit– und Geldmarktzins.
Keywords: E1; E5; G2; 330; Monetary policy transmission; credit market; leverage targeting; risk-taking channel; asset market shocks